Seasonal concentrations of cesium-137 in rumen content, skeletal muscles and feces of caribou from the Porcupine herd: lichen ingestion rates and implications for human consumption - Allaye-Chan, A. C.; White, R. G.; Holleman, D. F.; Russell, D. E. (Rangifer, 1990)
The Porcupine caribou herd was monitored for cesium-137 during 1987 to address human health concerns over potential meat contamination by radioactive fallout from the Chernobyl accident, and to determine lichen intake rates based on body burdens of radiocesium. A total of 36 caribou were collected from northwestern Alaska and the Yukon Territories in March, June, September, and November. Mean radiocesium concentrations in skeletal muscle peaked in March at 133 Bq/kg fresh weight. This value should not prove hazardous to human health. Radiocesium concentrations in skeletal muscle (wet weight) ranged from approximately 22 to 50% of radiocesium concentrations in rumen contents (dry weight), and from approximately 15 to 37% of radiocesium concentrations in feces (dry weight). Radioactivity in feces was significantly correlated with radioactivity in rumen contents. Computer simulations relating lichen intake rates to radiocesium body burdens are presented for 3 scenarios: (1) when seasonal intakes were adjusted to provide the optimum fit between simulated and observed radiocesium body burdens (2) when seasonal intakes were based on empirical data, and (3) when seasonal intakes were adjusted to yield a "conventional" radiocesium curve of a slow fall build-up prior to a late winter plateau.